2021
DOI: 10.1002/ece3.7885
|View full text |Cite|
|
Sign up to set email alerts
|

Plant‐eating carnivores: Multispecies analysis on factors influencing the frequency of plant occurrence in obligate carnivores

Abstract: Institute, 2020). Hence, understanding their dietary needs is an effective means to study the behavior, ecology, and evolutionary history of target species.Mammals can be roughly divided into three groups according to their diet: carnivores, omnivores, and herbivores. Plants are the primary food source of herbivores and are a relatively abundant resource in the environment. The composition of plant tissue is quite

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…Thus, we suggest that this species is not solely insectivorous, and individuals often supplement their diet with plant material. Many diet studies have reported plant material in carnivore and insectivore stomach content and scats (Yoshimura et al, 2021). Carnivorous mammals such as foxes, badgers civets, and insectivorous mammals such as aardvarks, and bats are reported to seasonally augment their diets with plant material such as berries, roots, nectar, and in some instances, foliage (Frick et al, 2014; Koike et al, 2008; Milton & Dean, 2001; Mudappa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that this species is not solely insectivorous, and individuals often supplement their diet with plant material. Many diet studies have reported plant material in carnivore and insectivore stomach content and scats (Yoshimura et al, 2021). Carnivorous mammals such as foxes, badgers civets, and insectivorous mammals such as aardvarks, and bats are reported to seasonally augment their diets with plant material such as berries, roots, nectar, and in some instances, foliage (Frick et al, 2014; Koike et al, 2008; Milton & Dean, 2001; Mudappa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…When constitutive defenses fail to prevent infections and illness, inducible (therapeutic) uses of plant substances could help bring infections under control, albeit with risk of poisoning. There is increasing evidence that invertebrates and vertebrates, including obligate carnivores, have evolved to co‐opt plant and fungal toxins to prevent or treat their own infections, a phenomenon termed self‐medication , zoopharmacognosy , or pharmacophagy (Boppré, 1984; de Roode et al, 2013; Huffman, 1997, 2017; Neco et al, 2019; Rodríguez & Wrangham, 1993; Villalba & Provenza, 2007; Wrangham & Nishida, 1983; Yoshimura et al, 2021). A systematic review of self‐medication in mammals found reports of self‐medication in 71 species from 7 mammalian orders, with the most reports in Primates (46 species), Carnivores (10 species), and Rodents (5 species).…”
Section: The Behavioral Immune System Includes Constitutive and Induc...mentioning
confidence: 99%
“…For example, their dentition is well-suited to crushing, cutting, grinding, and slicing meat [ 9 ], while their incisors, canines, premolars, molars, and carnassials are designed to hold their prey or pieces of meat [ 7 ]. They are also characterized by shorter, less complex digestive tracts with a lower capacity [ 10 ], since, unlike herbivores, their digestive processes do not require them to ferment food [ 11 ]. While dogs can eat plant-based foods, their anatomy preserves carnivorous traits of tearing muscle, crunching bones, and digesting meat more readily than plants [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on trends in human nutrition, this may expand further to include others such as hemp, oat, and bean proteins [ 13 ]. In contrast to animal tissues, plant cells are rich in carbohydrates (e.g., cellulose) that carnivores have difficulty digesting [ 11 ]. Proteins from cereal grains or soy contain lower amounts of essential amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation